2020
DOI: 10.3390/su12239989
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Antecedents of “Buy-Online-Pick-Up-In-Store” Service on Consumer’s BOPIS Choice Behaviour

Abstract: We studied the effect of the antecedents of the buy-online-pick-up-in-store (BOPIS) service on consumer’s BOPIS choice and shopping behaviour. The convenience of BOPIS benefits retailers and consumers; therefore, we used online surveys of consumers and the unified theory of acceptance and use of technology 2 (UTAUT2) model. The results of the study show that performance expectancy, trust, compatibility with BOPIS shopping, hedonic motivation and social influence affected the behavioural intentions in omni-chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Researchers defined this "click and collect" service offered by many retailers (e.g., Walmart, Target, Kohl's, Nordstrom, etc.) as buy-online-pickupin-store (BOPS) or reserve-online-pickup-and-pay-in-store (ROPS) [23][24][25]. BOPS and ROPS belong to the same category in Bell's [21] matrix, which is shopping and delivery hybrid, although BOPS is a more widely known shopping mode in the retail field.…”
Section: Theoretical Background and Hypotheses Development 21 Omni-channel Shopping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers defined this "click and collect" service offered by many retailers (e.g., Walmart, Target, Kohl's, Nordstrom, etc.) as buy-online-pickupin-store (BOPS) or reserve-online-pickup-and-pay-in-store (ROPS) [23][24][25]. BOPS and ROPS belong to the same category in Bell's [21] matrix, which is shopping and delivery hybrid, although BOPS is a more widely known shopping mode in the retail field.…”
Section: Theoretical Background and Hypotheses Development 21 Omni-channel Shopping Methodsmentioning
confidence: 99%
“…This study examined U.S. consumers' selection intentions of the three popular omnichannel shopping methods (i.e., BOPI, BOCP, and BIHD), and proposed that the four mediators (i.e., PHV, PUV, PR, and PBC) would directly influence the intentions of choosing the omni-channel shopping methods. Prior studies showed the connections between these mediators and consumers' behavioral responses, such as purchase intention, repatronage intention, channel selection intention, and channel switching intention [23,74,77,78,83,93]. Kim et al [16] found that hedonic motivation positively impacted consumers' behavioral intentions toward using BOPI.…”
Section: Behavioral Responses and Moderating Effect Of Perceived Covid-19 Vulnerabilitymentioning
confidence: 99%
“…Our key result is that offline retail stores contribute to the reduction of returns in the online channel, while not harming the sales of the online channel. Relative to the latter, theory indicates two possible mechanisms through which physical, offline, stores could influence online product purchases: by detracting customers from the online channel due to channel substitution (e.g., [33]), and by attracting customers to the online channel due to cross-channel promotion [34] and logistics services [35,36]. Our findings suggest that both effects are rather small and/or stay in balance.…”
Section: H5cmentioning
confidence: 82%
“…Both phenomena could explain why, especially in areas where online sales are relatively low, adding offline stores may thus boost online sales [23]. Next to the promoting function, the offline channel can have a logistics function by allowing customers to order online and pick up the ordered items in a physical store (BOPIS: buy online, pick up in store) [35,36]. Offering such logistics flexibility could further increase the attractiveness of ordering in the online channel.…”
Section: Purchasesmentioning
confidence: 99%
“…This in-store technology positively affects the customer purchase decision (Abebaw and Matukuta, 2018). Digital devices and services, such as digital screens and digital signage transform the consumer decision process about purchasing the fashion product (Kim et al, 2020a(Kim et al, , 2020b. Therefore, the following hypothesis has been proposed:…”
Section: Mobile Pos/digital Walletsmentioning
confidence: 99%